Evaluation and analysis of residual stresses due to foreign object damage - Duo, P; Liu, J; Dini, D; Golshan, M; Korsunsky, A (2007)
Foreign object damage (FOD) in gas turbine engines occurs due to the ingestion of small inorganic particles (small stones and sand particles). The damage caused to the blade leading edge may lead to premature crack initiation and ultimately blade failure due the action of time-varying tensile loads. The problem of evaluating the severity of FOD and the induced reduction of component life was investigated in the laboratory, by reproducing the damage conditions accurately and subjecting the impacted blade to fatigue loading simulating the service conditions. One particular aspect of post-FOD analysis focuses on the evaluation of residual stresses in the vicinity of the notch. Residual stresses play an important rôle in controlling the rate of crack initiation and propagation, and may be responsible for accelerated crack growth if they are tensile ahead of the incipient crack, or can cause retardation otherwise. The present study was aimed at experimental and numerical investigate the magnitude and spatial variation of residual stresses in this region. Experimentally, a gas gun was used to introduce the damage by firing a hardened steel cube "point first". Following impact the residual stresses were evaluated using two different experimental techniques involving X-ray diffraction: laboratory low energy monochromatic stress measurement, and high-energy white beam synchrotron stress measurement. The results are compared with the numerical model of the impact phenomenon that was constructed for a selected portion of the blade material, and from which the residual stress pattern following simulated impact was calculated using Bammann damage material model. Both sets of experimental measurements are critically compared with the numerical result, and the relationship between them is discussed. © 2006 Elsevier Ltd. All rights reserved.